2021
DOI: 10.1111/1471-0528.16992
|View full text |Cite
|
Sign up to set email alerts
|

Universal newborn screening for congenital cytomegalovirus infection: feasibility and relevance in a French type‐III maternity cohort

Abstract: In 62% of congenital cytomegalovirus infection cases, only universal neonatal screening in saliva can detect infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 39 publications
5
18
0
Order By: Relevance
“…In 7.4% of the infants with a CMV-DNA very low/low positive first saliva sample, the repeated saliva samples also resulted CMV-DNA positive with very low viral load (i.e., the maximum value of CMV-DNA detected was equal to 2.34 log 10 IU/ml). These findings in agreement with recent literature ( 17 20 ) showed that a definitive diagnosis of cCMV, avoiding unnecessary tests and waste of resources, is to be confirmed by investigating urine sample that remains the gold standard for the diagnosis of cCMV infection. However, the collection of urine samples can be difficult and time-consuming compared to the saliva collection ( 8 , 9 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In 7.4% of the infants with a CMV-DNA very low/low positive first saliva sample, the repeated saliva samples also resulted CMV-DNA positive with very low viral load (i.e., the maximum value of CMV-DNA detected was equal to 2.34 log 10 IU/ml). These findings in agreement with recent literature ( 17 20 ) showed that a definitive diagnosis of cCMV, avoiding unnecessary tests and waste of resources, is to be confirmed by investigating urine sample that remains the gold standard for the diagnosis of cCMV infection. However, the collection of urine samples can be difficult and time-consuming compared to the saliva collection ( 8 , 9 ).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, saliva sampling in newborn screening programs is easier and more practical. In this study, in line with others ( 16 , 20 , 21 ), a low overall percentage (1.7%) of false-positive saliva screening samples was observed, confirming the suitability of this testing methodology. It is known that a potential CMV-DNA contamination may result from the breastfeeding ( 9 , 22 , 23 ).…”
Section: Discussionsupporting
confidence: 91%
“…We believe that individual pediatricians are not "at fault" for these knowledge gaps. Unlike some other countries, [24][25][26][27] US medical professional organizations such as the American Academy of Obstetrics and Gynecology and the AAP have not yet prioritized cCMV prevention, diagnosis, and management in practice guidelines. 28 Without the AAP emphasizing the importance of cCMV diagnosis and management, outside of the most severe presentations, 29 pediatricians will continue to experience gaps in their cCMV knowledge and practices which may result in missed opportunities to diagnose and treat cCMV.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study highlight the critical need for systematic cCMV screening and testing programs to diagnose most infants with cCMV. Examples of such programs include hearing-targeted cCMV testing, in which all infants who fail their newborn hearing screening are then tested for cCMV, and universal/routine screening programs, in which all infants are screened for cCMV regardless of apparent risk factors [ 40 , 44 , 45 ]. Such programs have been found to be effective and acceptable in several studies [ 46 , 47 , 48 , 49 , 50 ], although the debate about cost-effectiveness persists [ 51 ].…”
Section: Discussionmentioning
confidence: 99%